2009
DOI: 10.1021/es8034945
|View full text |Cite
|
Sign up to set email alerts
|

Do Acid Volatile Sulfides (AVS) Influence the Accumulation of Sediment-Bound Metals to Benthic Invertebrates under Natural Field Conditions?

Abstract: The present study evaluates the influence of acid volatile sulfides (AVS) on accumulation of sediment-bound metals in benthic invertebrates under natural field conditions. Natural sediments, pore water, surface water, and two species of widespread benthic invertebrates (Chironomus gr. thummi and Tubifex tubifex) were collected from 17 historical polluted Flemish lowland rivers and measured for metal concentrations. Different sediment characteristics were determined (AVS, organic matter, clay content) and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 49 publications
(103 reference statements)
1
39
0
1
Order By: Relevance
“…Therefore applying this theory to metal remobilization studies would be proper only in the case that sulfides are not oxidized during elutriation (Di Toro et al, 1990;DurĂĄn et al, 2012). During the past years, much evidence has shown that benthic invertebrates can accumulate metals, even when [SEM]-[AVS] < 0, since benthic invertebrates ingest sediment particles as their main food source disregarding AVS (Lee et al, 2000a;Lee et al, 2000b;De Jonge et al, 2009;De Jonge et al, 2010). YHH3 YHH2 YHH1 GLH3 GLH2 GLH1 YHH-GLH ZMH2 ZMH1 ZM-YHH L1 L2 L3 L4 L5 MH6 MH5 XQH4 XQH3 XQH2 XQH1 K1 K2 K3 MH4 MH3 MH2 MH1 J1 J2 J3 J4 BLH3 BLH2 BLH1 I1 I2 I3 DH2 DH1 YH5 YH4 YH3 YH2 YH1 H1 H2 H3 WH3 WH2 WH1 JLH2 SEMs can be combined with AVS to reduce their toxicity; however, AVS of excessively high content is also harmful to aquatic organism.…”
Section: The Limitations Of Avs-sem Evaluation Methodsmentioning
confidence: 99%
“…Therefore applying this theory to metal remobilization studies would be proper only in the case that sulfides are not oxidized during elutriation (Di Toro et al, 1990;DurĂĄn et al, 2012). During the past years, much evidence has shown that benthic invertebrates can accumulate metals, even when [SEM]-[AVS] < 0, since benthic invertebrates ingest sediment particles as their main food source disregarding AVS (Lee et al, 2000a;Lee et al, 2000b;De Jonge et al, 2009;De Jonge et al, 2010). YHH3 YHH2 YHH1 GLH3 GLH2 GLH1 YHH-GLH ZMH2 ZMH1 ZM-YHH L1 L2 L3 L4 L5 MH6 MH5 XQH4 XQH3 XQH2 XQH1 K1 K2 K3 MH4 MH3 MH2 MH1 J1 J2 J3 J4 BLH3 BLH2 BLH1 I1 I2 I3 DH2 DH1 YH5 YH4 YH3 YH2 YH1 H1 H2 H3 WH3 WH2 WH1 JLH2 SEMs can be combined with AVS to reduce their toxicity; however, AVS of excessively high content is also harmful to aquatic organism.…”
Section: The Limitations Of Avs-sem Evaluation Methodsmentioning
confidence: 99%
“…Some researchers have displayed that benthic organism can accumulate metals in their body, even when SEM-AVS < 0, since benthic organism eats sediment particles as their major food source disregarding AVS concentration level (De Jonge et al 2009Lee et al 2000a, b). AVS values may vary when environmental conditions (such as pH, Eh, oxygen content, etc.)…”
Section: Assessment Of Sediment Toxicitymentioning
confidence: 99%
“…The AVS-SEM and TEL-PEL methods were all based on laboratory experiment while not field results (Hinkey and Zaidi 2007;HĂŒbner et al 2009;De Jonge et al 2009). A lot of researches have found that even the molar of SEM far larger than that of the AVS in sediments, whereas it still did not cause toxicity to benthic biota (Allen et al 1993;Ankely et al 1996).…”
Section: Multivariate Statistical Analysis Of Heavy Metalsmentioning
confidence: 99%